Original Research: The expression of MMP2 and MMP9 in the hippocampus and cerebral cortex of newborn mice under maternal lead exposure. Issue 16 (October 2016) - Li, Ning; Li, Xing; Li, Li; Zhang, Pingan; Qiao, Mingwu; Zhao, Qiuyan; Song, Lianjun; Yu, Zengli
The current study focused on the MMP2 and MMP9 expression in cerebral cortex and hippocampus of newborn mice under maternal lead exposure. Lead exposure was initiated from gestation to weaning. Lead acetate was dissolved in deionized water with concentration of 0.1, 0.2, and 0.5% and was absorbed through daily drinking. On day 21 after birth, lead in blood and tissue levels was examined by Graphite Furnace Atomic Absorption Spectrum (GFAAS). The protein expressions of MMP2 and MMP9 in hippocampus and cerebral cortex tissues were tested by western blotting and immunohistochemistry. Compared to the control group, blood, cerebral cortex, and hippocampus lead levels of newborn mice in 0.1, 0.2, and 0.5% lead exposure groups were markedly high ( P < 0.05), and mice within the 0.2 and 0.5% lead exposure groups performed much worse than that of the control group in Water Maze test ( P < 0.05). Compared with the control group, MMP2 and MMP9 expressions in hippocampus were up-regulated in the lead exposure groups ( P < 0.05), and the MMP2 and MMP9 expressions in cerebral cortex were also higher ( P < 0.05). The increased expression of MMP2 and MMP9 in the hippocampus and cerebral cortex may lead to the neurotoxicity in the context of maternal lead exposure.